MODELS OF FINANCING INNOVATIONS IN THE UKRAINIAN BUSINESS ENVIRONMENT (Development Service Industry Management, 2024)
The article examines various models of innovation financing that exist in the modern Ukrainian business environment, analyzing their advantages and disadvantages. The author describes in detail several main sources of financing: internal funds of enterprises, bank lending, venture financing, state financing and crowdfunding. In the context of each source, its role in supporting innovation is assessed, and the main challenges and perspectives for development are identified. Particular attention is paid to venture financing and its influence on the development of startups in the field of high technologies. The author emphasizes the importance of state support for innovative projects and the role of crowdfunding as an innovative method of attracting funds that allows entrepreneurs to test market demand and attract a wide audience to finance their ideas. The article highlights not only the current state of affairs in the field of financing innovations in Ukraine, but also offers recommendations for optimizing existing models and developing new approaches, with the aim of increasing efficiency and attracting additional resources to support innovative activity. The article emphasizes the need to adapt Ukrainian companies to the changing conditions of globalization, rapid technological progress and growing competition in international markets. It is worth noting separately the aspects of synergy between different sources of funding and their potential combination to achieve better results in innovative projects. For example, the possibility of combining government subsidies with venture capital investments or using crowdfunding campaigns to attract additional funding and test market validation of products. In conclusion, the article emphasizes the imperative of developing a comprehensive state policy in the field of innovation, which would include tax incentives, financial instruments and regulatory frameworks that will promote the development of the innovation ecosystem. The author calls for the creation of conditions that will not only help Ukrainian companies to survive, but also to prosper in the era of technological changes.
Keywords: innovation; business; digital technologies; business model; efficiency